The biting and predaceous midges of Guadeloupe (Diptera: Ceratopogonidae). II. Species of the subfamily Dasyheleinae - Grogan, Willliam L. Jr.; Díaz, Florentina; Spinelli, Gustavo R.; Ronderos, Maria M. (Zootaxa, 2016)
We provide descriptions, photographs and illustrations of 13 new species and new records of eight other species of biting midges in the genus Dasyhelea Kieffer from Guadeloupe. Included are the first Guadeloupe records of D. bermudae Wirth & Williams, D. caribbeana Spinelli & Wirth, D. cincta (Coquillett), D. flavifrons (Guérin-Méneville), D. grisea (Coquillett), D. griseola Wirth, D. luteogrisea Wirth & Williams and D. pseudoincisurata Waugh & Wirth. The previously unknown male of D. caribbeana is described and illustrated, and, a key is provided for the 24 species of Dasyhelea known from Guadeloupe.